Self-Confidence and Speaking Skills for Lower Secondary School Students: A Correlation Study - Aulia, Nisa Arifa Nurul; Apoko, Tri Wintolo (Journal of Languages and Language Teaching, 2022)
Self-confidence is a trait that can evoke an attitude to have positive, idealistic, and optimistic thoughts about abilities. Even though there are frequent interactions between teachers and students with English in class, students still feel less confident when speaking in front of their classmates. The study was aimed to investigate the relationship between EFL students' self-confidence and their speaking skills at SMPIT Al Muchtar. The type of this study is quantitative design. The IBM SPSS Statistics application with 24 version was used to calculate. The population taken was all the eighth grade students which consisted of 108 students. There were 30 students taken using the purposive sampling technique as the respondents comprising 22 females and 8 males. Two instruments were used to collect the data, namely: a questionnaire for measuring students’ self-confidence and speaking test used for speaking skills. After the data was obtained, the researcher analyzed the correlation data. It was found that there was a positive relationship between EFL students' self-confidence and speaking skills at SMPIT Al Muchtar. This proved that Ha was accepted and Ho was rejected because 0.548 > 0.361 with a significance value of 5%. In conclusion, there was a fairly significant relationship between self-confidence and speaking skill.